Efektivitas penggunaan alat peraga mini phantom panggul terhadap peningkatan pengetahuan, sikap dan keterampilan mahasiswa D3 kebidanan semester II di Akbid Harapan Keluarga Nias Tahun 2024 - Helena Mariani Sadawa; Hidayat Wijayanegara; Anita Deborah Anwar; Ma’mun Sutisna; M. Alamsyah Aziz; Siti Sugih Hartiningsih6 (Jurnal Riset Kebidanan Indonesia, 2025)
Background: Pelvic anatomy is an important part of obstetrics. The pelvis is the part of the body located below the abdomen and above the thighs, which involves a series of bones, joints, and other structures. A good understanding of pelvic anatomy is essential in midwifery practice because the pelvis plays an important role in the process of pregnancy and childbirth. However, there are obstacles for students in understanding pelvic anatomy, including the complexity of anatomical structures, clinical terms and vocabulary, anatomical visualization, limited learning resources, and discomfort with abstract materials. Research objectives: This study aims to prove the effectiveness of using a mini phantom pelvic prop on improving the knowledge, attitudes and skills of D3 Midwifery Semester II students at Akbid Harapan Keluarga Nias in 2024. Method: This type of research is an experiment with a Nonequivalent Control Group Design. The accessible population is D3 Midwifery semester II students at Akbid Harapan Keluarga Nias in 2024 as many as 70 students. The total sampling method is divided into 2 classes, namely the experimental class and the control class. Data analysis uses the Wilcoxon Signed Ranks test to see the differences between groups in SPSS. Results: The results of the study showed differences in knowledge, attitudes and skills between students who used the Mini Phantom Pelvic Teaching Aid and those who used learning videos. Conclusion: Based on the results of the N-Gain test, the mini phantom pelvic teaching aid was effective in increasing knowledge, but was not effective for the attitudes and skills of D3 Midwifery students Semester II at Akbid Harapan Keluarga Nias in 2024.